Potentiality of Acidithiobacillus thiooxidans in Microbial Solubilization of Phosphate Mine Tailings - S Dhakar; N Ali; R S Chauhan; V Yadav (Brawijaya University, 2015)
This paper deals with the solubilization behavior of the tailings produced by the floatation of a complex low grade phosphate ore. The composition of the tailings was essentially dolomite (52.04%) with minor amounts of phosphate, iron and aluminium oxides (10.4 and 0.5% respectively). The presence of these products created uncontrolled land pollution and severely affected groundwater. An initiative has been taken up for utilization of this waste to generate an eco-friendly product. First step towards this panorama is incorporation of suitable microorganisms for the biodegradation of this effluent. Sulphur oxidizing bacteria Acidithiobacillus thiooxidans produces sulphuric acid which neutralizes the dolomitic tailings and convert it into plant available forms. The solubilization activity was tested in sulphur medium with 5, 10, 15 and 20% concentration of tailings. The solubilization is graded on the basis of pH, Electrical conductivity (EC), soluble calcium and magnesium and soluble phosphate. The results from ex-situ experiments showed that the treatment with 15% tailings ended with highest solubilization. The values of pH, EC, soluble calcium and magnesium and soluble phosphate for this treatment were 4.92, 31.6 dS/m, 10.8 mL EDTA and 17.24 µg/mL respectively. Also, the results proved that sulphur oxidizing bacteria Acidithiobacillus thiooxidans is capable of solubilizing dolomitic tailings from the Jhamarkotra mines. Finally, an important factor taken into account wassolubilization of residual phosphate along with dolomite in the tailings. This combined action affects the solubilization behaviour of the residue, which was also showed successfully with the assayed laboratory studies.